STAT3 plays a critical role in KRAS-induced pancreatic tumorigenesis - Corcoran, Ryan B. (2011)
The STAT3 transcription factor is an important regulator of stem cell self-renewal, cancer cell survival, and inflammation. In the pancreas, STAT3 is dispensable for normal development whereas the majority of pancreatic ductal adenocarcinomas (PDAC) show constitutive activation of STAT3, suggesting its potential as a therapeutic target in this cancer. Here, we sought to define the mechanisms of STAT3 activation and its functional importance in PDAC pathogenesis. Large-scale screening of cancer cell lines with a JAK2 inhibitor that blocks STAT3 function revealed a >30-fold range in sensitivity in PDAC, and showed a close correlation of sensitivity with levels of tyrosine-phosphorylated STAT3 and of the gp130 receptor, an upstream signaling component. Correspondingly, upregulation of the IL6/LIF-gp130 pathway accounted for the strong STAT3 activation in PDAC subsets. To define functions of STAT3 in vivo, we developed mouse models that test the impact of conditional inactivation of STAT3 in KRAS-driven PDAC. We showed that STAT3 is required for the development of the earliest pre-malignant pancreatic lesions, acinar-to-ductal metaplasia (ADM) and pancreatic intraepithelial neoplasia (PanIN). Moreover, acute STAT3 inactivation blocked PDAC initiation in a second in vivo model. Our results demonstrate that STAT3 has critical roles throughout the course of PDAC pathogenesis, supporting the development of therapeutic approaches targeting this pathway. Moreover, our work suggests that gp130 and phospho-STAT3 expression may be effective biomarkers for predicting response to JAK2 inhibitors.